The Role of 5-ALA in Low-Grade Gliomas and the Influence of Antiepileptic Drugs on Intraoperative Fluorescence - Goryaynov, Sergey A.; Widhalm, Georg; Goldberg, Maria F.; Chelushkin, Danil; Spallone, Aldo; Chernyshov, Kosta A.; Ryzhova, Marina; Pavlova, Galina; Revischin, Alexander; Shishkina, Ludmila; Jukov, Vadim; Savelieva, Tatyana; et al. (Frontiers in Oncology, 2019)
Objectives Intraoperative tumor visualization with 5-aminolevulinic acid (5-ALA) induced protoporphyrin IX (PpIX) fluorescence is widely applied for improved resection of high-grade gliomas. However, visible fluorescence is present only in a minority of low-grade gliomas (LGGs) according to current literature. Nowadays, antiepileptic drugs (AEDs) are frequently administered to LGG patients prior to surgery. A recent in-vitro study demonstrated that AEDs result in significant reduction of PpIX synthesis in glioma cells. The aim of this study was thus to investigate the role of 5-ALA fluorescence in LGG surgery and the influence of AEDs on visible fluorescence. Patients and methods Patients with resection of a newly diagnosed suspected LGG after 5-ALA (25 mg/kg) administration were initially included. During surgery, the presence of visible fluorescence within the tumor and intratumoral fluorescence homogeneity were analyzed. Tissue samples from fluorescing and/or non-fluorescing areas within the tumor and/or the assumed tumor border were collected for histopathological analysis (WHO tumor diagnosis, cell density and proliferation rate). Only patients with diagnosis of LGG after surgery remained in the final study cohort. In each patient, the potential preoperative intake of AEDs was investigated. Results Altogether, 27 patients with a histopathologically confirmed LGG (14 diffuse astrocytomas, 6 oligodendrogliomas, 4 pilocytic astrocytomas, 2 gemistocytic astrocytomas and one desmoplastic infantile ganglioglioma) were finally included. Visible fluorescence was detected in 14 (52%) of 27. Cell density (p = 0.03) and proliferation rate (p =0.04) was significantly higher in fluorescence-positive than in fluorescence-negative samples. Furthermore, 15 (56%) of 27 patients were taking AEDs before surgery. Of these, 11 patients (73%) showed no visible fluorescence. In contrast, 10 (83%) of 12 patients without prior AEDs intake showed visible fluorescence. Thus, visible fluorescence was significantly more common in patients without AEDs compared to patients with preoperative AED intake (OR = 0,15 (CI 95% 0.012-1.07), р =0.046). Conclusions Our study shows a markedly higher rate of visible fluorescence in a series of LGGs compared to current literature. According to our preliminary data, preoperative intake of AEDs seems to reduce the presence of visible fluorescence in such tumors and should thus be taken into account in the clinical setting.